Gingival recession coverage with a modified tunnel connective tissue graft technique – case report - Matejkowski, Bartosz; Bogusławska-Kapała, Agnieszka; Strużycka, Izabela (Forum Ortodontyczne / Orthodontic Forum, 2018)
Gingival recessions are a more and more common pathology of multifactorial aetiology. They may affect individual teeth or be generalised. Studies have shown that the incidence of gingival recession increases with age. Recession is accompanied by loss of the connective tissue attachment and exposure of tooth root surfaces, what may lead to tooth hypersensitivity, root caries, non-carious defects, impaired control of the dental plaque and unsatisfactory aesthetic outcomes. Aim. The aim of the paper was to present treatment of a female patient with advanced gingival recessions in the area of upper canines with a modified tunnel technique, with a free connective tissue graft taken from the palate. Material and methods. Treatment included a surgical method of gingival recession treatment consisting of a modified tunnel technique, with a free connective tissue graft harvested from the palate that was introduced via a tunnel into the donor site. Results. 2 years after the procedure recession coverage and increased zone of the attached gingiva was observed. Conclusions. The modified tunnel connective tissue graft technique used to treat the gingival recession allowed to achieve satisfactory aesthetic outcomes and effective elimination of hypersensitivity, and it reduced the risk of tooth caries. (Matejkowski B, Bogusławska- Kapała A, Strużycka I. Gingival recession coverage with a modified tunnel connective tissue graft technique – case report. Orthod Forum 2018; 14: 344-52).